Effect of phosphorus dopant concentration on the carrier mobility in crystalline silicon - Ayele, Yasab; Yohannes, Zena; Benor, Amare (Ethiopian Journal of Science and Technology, 2025)
This study investigated the effect of phosphorus dopant concentration on mobility of crystalline silicon (c-Si). It considers different temperature ranges, from 100 K to 500 K, and dopant concentration from 1012 cm-3 to 1020 cm-3 in relation to its effect on the mobility of the crystalline silicon. This study indicates that the mobility of phosphorus doped silicon, n-type silicon, at different dopant concentration, tends to reduce as the temperature is increased. On the other hand, the mobility of the doped semiconductor, at different temperatures, showed different trends as the dopant concentration increases: I) mobility decreased in between 1015 to 1017 cm-3, II) mobility saturates doping concentrations less than 1014 cm-3, and III) mobility is not significantly affected, by increasing the temperature for high doping concentration 1018 to 1020 cm-3. The two issues, lattice and impurity, dominate one another depending on the doping concentration and temperature, and thus contributed to dependence of mobility on temperature, in different trend, while being dependent on the fundamental theory of doping in semiconductors. Based on the study, as the temperature gets higher for higher doping concentration, mobility by the impurity scattering increases while it decreases by the lattice scattering, the two cases balance one another, and as a result mobility becomes almost constant, that is, the rate of change of mobility is relatively insignificant.